P54 Symptom status and postal kit return rates of individuals accessing an online sexually transmitted infection (STI) testing service. (16th June 2022) - Goward, Charlotte; Apea, Vanessa; White, John; Clune, Mark; Day, Sara
Abstract : Background: Online sexual health services (e-services) are being increasingly used for STI testing. Reduced sexual health clinic capacity due to the Covid-19 pandemic prompted our regional e-service to widen eligibility and enable individuals with mild symptoms to access our service. Prior to placing a kit order, information was shown to all symptomatic service users, advising them of the benefits of attending a sexual health clinic and/or to attend a clinic if symptoms persist/worsen. Method: A retrospective analysis was performed of service users that ordered a testing kit between March 2020, and December 2021. Kit return rates were compared according to symptom status. Results: Of 888, 619 kit orders 163, 023 (18.3%) came from symptomatic users. The most common symptom reported was vaginal discharge (41.1%), followed by dysuria/frequency (18.4%) and itching (13.8%). The kit return rate among asymptomatic service users was significantly higher (79.3%) compared to symptomatic users (74.3%) (X2 6.04. p =0.01401). The highest return rates were seen among individuals with itching (75.8%), dysuria/frequency (75.7%) and vaginal discharge (74.6%). The lowest return rate was seen by individuals with genital lumps (71.2%). Discussion: Significantly fewer kits were returned by symptomatic e-service users compared to asymptomatics. It is plausible the e-service advisory information deterred some users from returning kits, encouraging them to instead test at a clinic. However, many users opted to complete testing online or perhaps did so because of difficulty accessing a sexual health clinic. Further work is needed to explore the preferred modality of testing provider and the suitability of online services for symptomatic individuals.